Should treatment decisions in septic arthritis of the native hip joint be based on the route of infection? - F. Ruythooren; F. Ruythooren; S. Ghijselings; S. Ghijselings; J. Cools; J. Cools; M. Depypere; P. De Munter; P. De Munter; W.-J. Metsemakers; W.-J. Metsemakers; G. Vles; et al. (Journal of Bone and Joint Infection, 2023)
Background: Surgical management of septic arthritis (SA) of the hip aims at treating the infection by either preserving, resecting or replacing the joint. In some cases, joint preservation should be attempted, whereas other cases would benefit from immediate joint resection or replacement. Prognostic factors have been proposed to guide decision-making. We hypothesized that most of these factors can be simplified to three subgroups based on the route of infection: contiguous spreading, direct inoculation or hematogenous seeding. Methods: A total of 41 patients have been treated surgically for SA of the native hip at our tertiary hospital during the last 16 years. Medical records were studied, and various patient and disease characteristics were collated. Results: Significant differences between (1) level of fitness, (2) condition of the hip joint, (3) micro-organisms and (4) chance of femoral head preservation were found for patients with SA of the native hip resulting from the three aforementioned subgroups. Femoral head resection was necessary at one point in 85 % of patients. Patients with hematogenous infections of undamaged hips had a reasonable chance (53 %) of avoiding joint resection or replacement. Hip arthroplasty was performed on 46.3 % of patients, with an infection rate of 10.5 %. Conclusion: Patients with SA of the native hip resulting from contiguous spreading, hematogenous seeding or direct inoculation differ significantly and should be considered distinct clinical entities. Route of infection is directly related to the chance of femoral head preservation and should, therefore, guide decision-making. Only patients with hematogenous infection to a previously healthy hip had the possibility of femoral head preservation.